HUBUNGAN TINGKAT KEPUASAN IBU HAMIL TERHADAP PELAYANAN ANC DENGAN MOTIVASI UNTUK MELAKUKAN ANC DI KELURAHAN PURWOKERTO KULON WILAYAH KERJA PUSKESMAS PURWOKERTO 2 SELATAN KABUPATEN BANYUMAS - Fitria Zuhriyatun; Tuni Candra Dewi (Viva Medika, 2009)
Background: One of the efforts to accelerate the reduction in maternal mortality and infant is the approach to maternal and neonatal health services quality, thatdo visit antenatal or Antenatal Care (ANC).Objective: To determine the relationship between the level of satisfaction ofpregnant women to antenatal care with motivation do antenatal care.Methods: This study was descriptive correlation with cross sectional approach.The sampling technique used was accidental sampling. Samples were pregnantwomen, a number of 30 respondents.Results: From the results, the majority of pregnant women to the level ofsatisfaction of antenatal care services is quite satisfied as much as 15 respondents(50%), and most of the motivation of respondents are currently as many as 15respondents (50%).Conclusion: There is a relationship between satisfaction pregnant women toantenatal care with the motivation to do antenatal care in Purwokerto Kulonvillage in 2012 with Ï-value <Î± (0.000 <0.05). Keywords: Satisfaction Pregnancy, Antenatal Care, Motivation Antenatal Care